ANDROID-BASED-GAME AND BLENDED LEARNING IN CHEMISTRY: EFFECT ON STUDENTS’ SELF-EFFICACY AND ACHIEVEMENT - Nur Fitriyana; Antuni Wiyarsi; Jaslin Ikhsan; Kristian Handoyo Sugiyarto (LPMPP Universitas Negeri Yogyakarta, 2020)
The 21st century learning system demands the use of technology in learning instruction. This research focuses on the comparison between the use of android-based-game and blended learning in the Chemistry subject on the hydrocarbon lesson toward students’ self-efficacy and achievement. A quasi-experiment with post-test only design was adopted in this research. A number of 143 eleventh graders from two public senior high schools in Purworejo Regency, Indonesia were selected in a cluster random sampling as the research sample. The sample was classified into three groups depending on the media used, i.e. android-based-game only on face-to-face learning (ABG-FTFL), blended learning only (BL), and both android-based-game and blended learning (ABG-BL). Self-Efficacy Scale (SES) was used to obtain the data of students’ self-efficacy while the hydrocarbon test was used to obtain students’ achievement. One-way Analysis of Variance, Kruskal Wallis test, and descriptive quantity technique were performed in the data analysis, and it is found that the use of these technologies has a significant effect on the students’ self-efficacy and achievement. The use of ABG-BL is better in improving students’ self-efficacy while BL is better in enhancing students’ achievement. Therefore, the use of android-based-game and blended learning can be emphasized as media in chemistry learning to gain better self-efficacy and achievement among students.